2017
DOI: 10.1017/s1368980017000763
|View full text |Cite
|
Sign up to set email alerts
|

Are more environmentally sustainable diets with less meat and dairy nutritionally adequate?

Abstract: Diets with all meat and dairy replaced with plant-based foods lowered environmental impacts by >40 %. Estimated intakes of Zn, thiamin, vitamins A and B12, and probably Ca, were below recommendations. Replacing 30 % was beneficial for SFA, Na, fibre and vitamin D intakes, neutral for other nutrients, while reducing environmental impacts by 14 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 29 publications
2
62
0
Order By: Relevance
“…This is consistent with previous studies in Ireland [ 9 ], the Netherlands [ 7 ] and France [ 8 ]. Thus, this study provides further evidence based on self-selected diet that reducing meat consumption is likely to contribute to lower diet-related GHGE [ 2 ], as indicated in modeling studies [ 49 , 54 , 55 ]. Nevertheless, avoidance or lower intake of animal foods such as red meat may also contribute to nutritional inadequacy of several micronutrients such as iron, zinc and vitamin B-12 [ 56 ].…”
Section: Discussionmentioning
confidence: 71%
“…This is consistent with previous studies in Ireland [ 9 ], the Netherlands [ 7 ] and France [ 8 ]. Thus, this study provides further evidence based on self-selected diet that reducing meat consumption is likely to contribute to lower diet-related GHGE [ 2 ], as indicated in modeling studies [ 49 , 54 , 55 ]. Nevertheless, avoidance or lower intake of animal foods such as red meat may also contribute to nutritional inadequacy of several micronutrients such as iron, zinc and vitamin B-12 [ 56 ].…”
Section: Discussionmentioning
confidence: 71%
“…For example, further impact mitigation in high-income nations may be achieved by lowering the recommendations for dairy, which remains an important contributor of GHG emissions in many nations even under recommendation-compliant diets. However, although partial replacement of meat and dairy by plant-derived food sources does not substantially change the adequacy of nutrient intake ( 34 , 35 ), the extent to which this can be applied in NRDs and then extrapolated globally needs to be established. Furthermore, in high-income nations, countries with high fish intake (Mediterranean and Scandinavia) show large reductions in land use relative to other nations.…”
Section: Resultsmentioning
confidence: 99%
“…These observations are in line with the results of our study: some individual food groups, for instance, cereals, may have an important environmental impact in Mediterranean countries because they are consumed in a higher quantity; moreover, in our study we found that consumption of meat was slightly higher among individuals with the eco-friendliest dietary habits, suggesting a general low consumption of meat (especially processed) in this population in spite of a high intake of dairy products. Interestingly, a study argued that while dietary patterns with all meat and dairy replaced with plant-based foods would lower environmental impacts, estimated intakes of zinc, thiamin, vitamins A, and B12, and probably calcium, would be below recommendations; thus, replacing 30% of the aforementioned food groups would result beneficial for saturated fatty acids, sodium, fiber, and vitamin D intakes, neutral for other nutrients, while reducing environmental impacts [50]. Notably, despite that there is agreement among current scientific literature on the topic, there are also other points of view to be considered when examining our results.…”
Section: Discussionmentioning
confidence: 99%